Effect of root length over alveolar bone on fracture resistance: Detection by cone-beam computed tomography - Fumi Mizuhashi; Ichiro Ogura; Yoshihiro Sugawara; Makoto Oohashi; Hirokazu Sekiguchi; Hisato Saegusa (Wolters Kluwer Medknow Publications, 2019)
Background/Aim: The aim of this study was to investigate the influence of root length over alveolar bone to the occurrence of root fracture using cone-beam computed tomography (CBCT). Methods: We reviewed the CBCT images of 176 endodontically treated upper incisors (7 with root fracture and 169 without root fracture) from April 2018 to March 2019. Measurement of the mesial and distal root length over and under the alveolar bone was performed by cross-sectional multiplanar reformation (MPR) image that passing the middle of the distance from the labial side to the palatal side of the tooth, and measurement of the labial and palatal root length over and under the alveolar bone was performed by parasagittal MPR image that passing the middle of the distance from the mesial side to the distal side of the tooth using CBCT. The minimum and average values among the labial, palatal, mesial, and distal root length over and under the alveolar bone were evaluated. The minimum and average values of the root length ratio of over the alveolar bone to under the alveolar bone were also evaluated. Statistical analysis was performed by Mann-Whitney U-test. Results: The minimum and average values of root length over the alveolar bone were statistically significantly different between the tooth with and without root fracture (P < 0.01). The minimum value of the root length ratio of over the alveolar bone to under the alveolar bone was statistically significantly different between the tooth with and without root fracture (P < 0.001). Conclusions: These results suggested that the root length over the alveolar bone was smaller in the tooth with root fracture.